Pengaruh Positive Word-Of-Mouth, Customer Trust, Dan Customer Value Terhadap Revisit Intention Yang Dimediasi Oleh Customer Loyalty Pada Rumah Sakit - Riady, Chelsea; Kristaung , Robert (Fakultas Ekonomi Universitas Gresik, 2023)
These days hospitals have turned into an institution which is more business-oriented, so patients experiences become important for a competitive growth strategy, which includes positive word-of-mouth, customer trust, value, and loyalty. This study was conducted to analyze the effect of positive word-of-mouth, customer trust, and customer value on revisit intention mediated by customer loyalty in type B publicly-traded hospitals. This study used a questionnaire from 202 respondents distributed using a purposive sampling technique. Hypothesis analysis by the use of a partial least square (PLS) test, which is one of the structural equation modeling (SEM) approaches. First, a measurement model test was carried out by testing the validity and reliability of each indicator, and a structural model was also carried out to determine the relationship between variables in the model. The results showed that there are positive effects of positive word-of-mouth, customer trust, and customer value on customer loyalty, and there is also a positive effect of customer loyalty on revisit intention. In addition, it is also found that customer loyalty mediates the effect of positive word-of-mouth, customer trust, and customer value on revisit intention